ASSESSMENT OF PARAMETRIC AND NON-PARAMETRIC METHODS FOR SELECTING STABLE AND ADAPTED SPRING BREAD WHEAT GENOTYPES IN MULTI - ENVIRONMENTS - Hasan Klç (Journal of Animal and Plant Sciences, 2012)
The objectives of this research were to assess genotype-environment interaction (GEI) and to determine stable bread wheat (Triticum aestivum L.) genotypes for grain yield in the South-Eastern Anatolia region of Turkey during the 2004- 2007 growing seasons. Twenty five bread wheat genotypes were evaluated in a randomized complete block design with 4 replications. Genotypes, environments main effects and GEI were significant at P < 0.01. Both parametric (bi, S2 di, Ri2 , Wi2 , Si2 , CVi, σi2 , P59, αi, λi and Pi) and non-parametric (Si(1), Si(2) Si(3) Si(6), TOP and RS) univariate stability statistics were used to determine stability of the bread wheat genotypes. Genotypes G16, G6, G3, G5 and G20 were the most stable based on parametric and non-parametric stability measures used. The level of association among the stability measures was assessed using Spearman's rank correlation. The rank correlation matrix indicated that most non-parametric measures were significantly inter-correlated with parametric measures and therefore can be used as alternatives.
Keywords: Bread wheat; GE interaction; grain yield; parametric and non-parametric measures and stability